TAM Towards Leddite Building Mandors In The Use Of E-Filing - Permadi Setyo Wibowo Sungkono (Jurnal Akuntansi, 2020)
This study aims to identify perceptions of usefulness, convenience and attitude towards behavior in the use of e-filling. Data from this study were obtain through quesstionnaires distributed to the community in the category of technological stuttering and had produced 50 respondents consisting of construction foremen in PT. Hutama Karya (Persero) Surabaya Brach. This study had a result that found if the variable perceeived usefullness and perceived easse of being has a possitive and siignificant effecct onthe use of, e-filling, but the attitude towards the most behavior did not affect the use of e-filling. This study hal limitation is that it only uses 1 company as a research sample, so it is less able to generalize these findings.